Analysis of The Application of Block Games in Developing Early Childhood Fine Motor Skills During the Covid-19 Pandemic In Tk Dharma Bahagia Samarinda School Year 2020 - Fachrul Rozie; Budi Rahardjo; Sanbayu Maya (Tajdid Al-Athfal, 2022)
This study aims to describe the application of playing blocks during the COVID-19 pandemic. This research method is qualitative with descriptive research type. The subject of this research was carried out on Kindergarten students aged 5-6 years at Dharma Bahagia Kindergarten Samarinda for the 2020 academic year which consisted of 3 students. The data analysis technique used is the Milles and Hubberman model. The results of the study illustrate that the planning carried out in the block game aims to develop fine motor skills. The teacher asks for the willingness of parents as facilitators to prepare tools in the block game. Optimizing children's fine motor skills in terms of the way the teacher carries out teaching activities, it can be seen that the teacher applies learning steps by providing the direction of the block game through the zoom application. However, the stimulation provided by the teacher in the development of fine motor skills with this bold block game is still not optimal because of the obstacles that cannot be met face-to-face and parents also have to play a role in helping children. This study implies that the application of block games still needs to be done with variations in learning during the current pandemic.